Manejo de irrigação e nitrogênio no feijoeiro comum cultivado em sistema plantio direto - Lopes, Adriano da Silva; de Oliveira, Gabriel Queiroz; Souto Filho, Sebastiao Nilce [UNESP]; Goes, Renato Jaqueto [UNESP]; Camacho, Marcos Antonio (Univ Federal Ceara, Dept Geol, 2011)
With technological innovations, such as irrigation, the bean has been grown by producers who have the most varied levels of technology that, in suitable times, allows the planting great success in grain yield. The aim of this study was to evaluate the response of the dry bean to different managements of irrigation and nitrogen fertilization with no-tillage system, in Aquidauana - MS, Brazil. The experiment was conducted at the Universidade Estadual de Mato Grosso do Sul (UEMS), with the soil of the area classified as Alfisol, using the bean crop "Perola" sown on June 30, 2007. The experimental design was a randomized block split-plot consisting of three blocks and two replications within each block. The plots were composed of three management of irrigation, by the Class A pan method, using Hargreaves-Samani equation, and management by tensiometry (-40 kPa), with water replacement of 16.5 mm for all irrigation plots. The subplots consisted on four rates of nitrogen fertilization (0; 50; 100 and 150 kg ha(-1)), in which the nitrogen source was urea. It was concluded that the irrigation management through the Class A pan and Hargreaves-Samani equation conduced to higher grain yields of bean, 3031.11 and 3005.02 kg ha(-1) respectively.
Irrigation and nitrogen management in the dry bean-crop no tillage system
Keywords: Phaseolus vulgaris; Class A pan; Evapotranspiration; Urea